Candida utilis catheter-related bloodstream infection - Giancarlo Scoppettuolo; Concetta Donato; Elena De Carolis; Antonietta Vella; Luisa Vaccaro; Antonio La Greca; Massimo Fantoni (Medical Mycology Case Reports, 2014)
Central venous catheter-related fungemia are increasing in the last years, also due to rare fungi. We report the case of a Candida utilis catheter-related bloodstream infection in a patient with metastatic carcinoma of the bladder and a long term totally implanted venous catheter. The diagnosis was done by paired blood cultures and differential time to positivity. The Candida species was rapidly identified by MALDI-TOF mass spectrometry. The patient was successfully treated with anidulafungine.